A critique of hemispherology, modality preference and learning styles - Pillar Wesley Granville; Піллар Везлі Гренвілл („RIK-U” Kft., 2018)
Abstract. In the quest to find ways to aid cognition, there have been many attempts to correlate hemispheres of the brain with learner modality preference. The term “hemispherology” [Grinder, 1989] has been coined in an endeavour to classify learners in terms of their cerebral dominance (sometimes referred to as hemispheric specialisation, i.e. right hemisphere or left hemisphere) and modality preference (visual, audio or kinaesthetic - VAK). This approach to learner classification has spawned such terms as “ right brain learner”, “left brain learner”, “visual learner”, “auditory learner” and “kinaesthetic learner”, all of which, for better or for worse, are now common place in the learning/teaching environment. It is theorised by proponents of perceptual learning preferences [e.g. Dunn and Dunn, 1979] that visual learners learn better through what is read or seen, auditory learners learn better through what is heard, and kinaesthetic learners are more successful in learning through personal involvement (doing).
https://kmf.uz.ua/wp-content/uploads/2018/11/Multicult-Diversity_Book-of-Abstracts_23-10-2018.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00006453
Keywords: hemispherology; learning styles; modality preference